Lexical difficulty – using elicited imitation to study child L2. (April 2017) - Campfield, Dorota E.
This paper reports a post-hoc analysis of the influence of lexical difficulty of cue sentences on performance in an elicited imitation (EI) task to assess oral production skills for 645 child L2 English learners in instructional settings. This formed part of a large-scale investigation into effectiveness of foreign language teaching in Polish primary schools. EI item design and scoring, IRT and post-hoc lexical analysis of items is described in detail. The research aim was to resolve how much the lexical complexity of items (lexical density, morphological complexity, function word density, and sentence length) contributed to item difficulty and scores. Sentence length, as number of words, predicted better than number of syllables. Function words also contributed, and their importance to EI item construction is discussed. It is suggested that future research should examine phonological aspects of cue sentences to explain potential sources for variability. EI is shown to be a reliable and robust method for young L2 learners with potential for classroom assessment by teachers for emergent oral production skills.